2014
DOI: 10.1007/s40271-014-0054-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Stated Preferences for Colorectal Cancer Screening: A Critical Systematic Review of Discrete Choice Experiments

Abstract: Understanding and incorporating individuals' preferences in decision making is increasingly considered essential in the health field. Data from DCEs can provide valuable insights into the trade-offs individuals are willing to undertake in respect to CRC screening. Such insights can be used by decision makers to identify screening tests that could maximize informed uptake. It is likely that, with better reporting and evolving methodology, the contribution that DCEs can make to such debates will increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 47 publications
3
46
0
Order By: Relevance
“…2013Umar [35]2012Elicitation & use of patients’ preferencesin the treatment of psoriasis: a systematic review“To critically review the scientific evidence regarding the elicitation & use of patients’ preferences in psoriasis treatment.”Nov. 2009Van Brunt [10]2011Preferences related to attention-deficit/hyperactivity disorder & its treatment“To identify & summarize published research on preferences related ADHD & its treatment, while suggesting directions for future research.”UnclearVon Arx [36]2014The patient perspective of diabetes care:a systematic review of stated preference research“To examine how stated preference methods are applied in diabetes care, & to evaluate the value of this information in developing the patient perspective in clinical & policy decisions.”May 2013Wilke [37]2016Patient preferences for oral anti-coagulation therapy in atrial fibrillation:a systematic literature review“To systematically analyse the scientific literature assessing the preferences of AF patients with regard to long-term oral anticoagulant treatment.”2015Wortley [38]2014Assessing stated preferences for colorectal cancer screening: a critical systematic review of discrete choice experiments“To undertake a systematic review of discrete choice experiments of CRC screening.”April 2013 ADHD Attention-deficit/hyperactivity disorder, AF Atrial fibrillation, BPH Benign prostatic hyperplasia, BWS Best-worst scaling, COPD Chronic obstructive pulmonary disease, CRC Colorectal cancer, DCE Discrete choice experiment, NSCLC Non-small-cell lung cancer, SGI Standard gamble interview, TTO Time trade-off …”
Section: Resultsmentioning
confidence: 99%
“…2013Umar [35]2012Elicitation & use of patients’ preferencesin the treatment of psoriasis: a systematic review“To critically review the scientific evidence regarding the elicitation & use of patients’ preferences in psoriasis treatment.”Nov. 2009Van Brunt [10]2011Preferences related to attention-deficit/hyperactivity disorder & its treatment“To identify & summarize published research on preferences related ADHD & its treatment, while suggesting directions for future research.”UnclearVon Arx [36]2014The patient perspective of diabetes care:a systematic review of stated preference research“To examine how stated preference methods are applied in diabetes care, & to evaluate the value of this information in developing the patient perspective in clinical & policy decisions.”May 2013Wilke [37]2016Patient preferences for oral anti-coagulation therapy in atrial fibrillation:a systematic literature review“To systematically analyse the scientific literature assessing the preferences of AF patients with regard to long-term oral anticoagulant treatment.”2015Wortley [38]2014Assessing stated preferences for colorectal cancer screening: a critical systematic review of discrete choice experiments“To undertake a systematic review of discrete choice experiments of CRC screening.”April 2013 ADHD Attention-deficit/hyperactivity disorder, AF Atrial fibrillation, BPH Benign prostatic hyperplasia, BWS Best-worst scaling, COPD Chronic obstructive pulmonary disease, CRC Colorectal cancer, DCE Discrete choice experiment, NSCLC Non-small-cell lung cancer, SGI Standard gamble interview, TTO Time trade-off …”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review about preferences in the averagerisk population failed to conclude which test was preferred because of a high heterogeneity across the studies. 73 However, most studies agree that the preferred test should be sufficiently sensitive, it should last a short time, it should not require bowel preparation and it should entail no risk of complications. As this type of test does not exist, there was no single strategy that was unanimously preferred.…”
Section: Screening Preferencesmentioning
confidence: 99%
“…Understanding the preferences of the eligible population with regard to attributes of screening policies may help policymakers to further design the screening by selecting those attribute levels that maximize screening attendance. In addition, it will help policymakers to tailor information provision for people targeted for the screening [9]. Achieving high attendance (particularly of high-risk subpopulations) is important to realize the reduction in cancer-related mortality suggested in cancer screening trials.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed alongside lung cancer screening trials reported that smoking status, perceived risk of lung cancer, and result of baseline computed tomography scan were indicative of adherence to the screening protocol [10][11][12][13][14]. To obtain quantitative insights into the relative importance of attributes of lung cancer screening, stated preference methods can be used [9,15,16]. Stated preference questionnaires present respondents with direct questions about their preferences or have respondents make hypothetical decisions from which preferences are subsequently inferred.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation